New Species Of Hemicoelinum Espanol, 1971 (Coleoptera: Ptinidae) from Chile - Fierro-Tapia, C (SOC CHILENA ENTOMOLOGIA, 2023)
A new species of Anobiinae (Coleoptera: Ptinidae) of the genus Hemicoelinum Espanol, 1971, H. ornatus sp. n. is described, based on specimens collected in central and southern Chile. Diagnostic characters of the new taxon are indicated, mainly those contained in the pronotum, elytra, and pilosity. Photographs of the adult and of the male and female genitalia are presented.